A prospective assessment of the effect of aminophylline therapy on urine output and inflammation in critically ill children - Tamburro, Robert F.; Thomas, Neal J.; Ceneviva, Gary D.; Dettorre, Michael D.; Brummel, Gretchen L.; Lucking, Steven E. (Frontiers in Pediatrics, 2014)
Background: Aminophylline, an established bronchodilator, is also purported to be an effective diuretic and anti-inflammatory agent. However, the data to support these contentions are scant. We conducted a prospective, open-label, single arm, single center study to assess the hypothesis that aminophylline increases urine output and decreases inflammation in critically ill children. Methods: Children less than 18 years of age admitted to the pediatric intensive care unit who were prescribed aminophylline over a 24-hour period were eligible for study. The use and dosing of aminophylline was independent of the study and was at the discretion of the clinical team. Data analyzed consisted of demographics, diagnoses, medications, and markers of pulmonary function, renal function and inflammation. Data were collected at baseline and at 24-hours after aminophylline initiation with primary outcomes of change in urine output and inflammatory cytokine concentrations. Results: Thirty-five patients were studied. Urine output increased significantly with aminophylline use (median increase 0.5 mL/kg/hour ([IQR:-0.3,1.3], p=0.05) while BUN and creatinine concentrations remained unchanged. Among patients with elevated C-reactive protein concentrations, levels of both interleukin-6 (IL-6) and IL-10 decreased at 24-hours of aminophylline therapy. There were no significant differences in pulmonary compliance or resistance among patients invasively ventilated at both time points. Side effects of aminophylline were detected in 7 of 35 patients. Conclusions: Although no definitive conclusions can be drawn from this study, aminophylline may be a useful diuretic and effective anti-inflammatory medication in critically ill children. Given the incidence of side effects, the small sample size and the uncontrolled study design, further study is needed to inform the appropriate use of aminophylline in these children.